1993
DOI: 10.1515/cclm.1993.31.8.525
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Reference Ranges for Cortisol in Neonates, Infants, Children and Adolescents

Abstract: Summary:Cortisol was determined in the sera of 687 normal, healthy probands between the ages of 5 days and 18 years (neonates, infants, children and adolescents), using a fluorescence polarization immunoassay (FPIA) on the TDx from Abbott Laboratories. The proband collective was divided into 9 age groups and each group into males and females. In accordance with the recommendations of the International Federation of Clinical Chemistry, the 95% scatter range was taken as the reference range. Only a few reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
3

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 3 publications
3
20
3
Order By: Relevance
“…We found a difference in salivary cortisol levels between males and females with lower cortisol levels in males, as was reported in the 14-15 years age group in the large study by Jonetz-Mentzel and Wiedemann [30]. Age was not related to early morning cortisol in our study, which is expected given the narrow age-range of our study population.…”
Section: Discussionsupporting
confidence: 85%
“…We found a difference in salivary cortisol levels between males and females with lower cortisol levels in males, as was reported in the 14-15 years age group in the large study by Jonetz-Mentzel and Wiedemann [30]. Age was not related to early morning cortisol in our study, which is expected given the narrow age-range of our study population.…”
Section: Discussionsupporting
confidence: 85%
“…It was previously shown that diurnal salivary cortisol levels increase during middle childhood and adolescence [21] . Studies of an adolescent sample of 229 boys and 181 girls who were assessed consecutively at the mean ages of 15.0 (SD = 0.4), 16.0 (SD = 0.4) and 17.0 (SD = 0.4) years showed a positive correlation between salivary cortisol awakening and age progress [22,23] . In the present study, we showed that the cortisol levels increased with age from 4 to 19 years for both boys and girls.…”
Section: Discussionmentioning
confidence: 96%
“…The development of the HPA axis extends from childhood through adolescence, leading to different hormonal secretion patterns among prepubertal and postpubertal children, adolescents and adults [14] . An increment in cortisol levels has been linked to age and puberty progression [15][16][17] . Cortisol values show a gender differentiation in the final pubertal maturation stages [18,19] .…”
Section: Discussionmentioning
confidence: 99%
“…The circadian cortisol rhythm in children develops between 1 month and 2 years of age [15][16][17][18][19][20][21][22][23][24][25][26]. Although interindividual variability in cortisol levels has been related to age or pubertal status [24,27,28], the overall circadian pattern is very robust [25,29]. Therefore, data of children and adults were compared to the same cortisol curve obtained from Weitzman et al [30].…”
Section: Discussionmentioning
confidence: 99%